Hydrolyzed microalgae from biorefinery as a potential functional ingredient in Siberian sturgeon (A. baerii Brandt) aquafeed - T. Bongiorno; L. Foglio; L. Proietti; M. Vasconi; V. M. Moretti; A. Lopez; D. Carminati; A. Galafat; A. J. Vizcaíno; F. G. Acién Fernández; F. J. Alarcón; K. Parati (Algal Research, 2022)
The development of sustainable and functional feed represents an opportunity and a need for the aquaculture industry, supporting beneficial physiological effects on fish that go beyond traditional feed formulations. This study aims to evaluate the potential application of microalgae, produced through a sustainable process, as a functional ingredient in practical diets for Siberian sturgeon (Acipenser baerii) fingerlings. For this purpose, the effects of the dietary administration of two different microalgae, Nannochlopsis gaditana and Scenedesmus almeriensis, cultivated on conventional synthetic medium (SM) or diluted pig manure (PM) and included in diets as crude or hydrolyzed biomasses, were tested. Growth performance and oxidative status of the fish were evaluated and compared in relation to the different diets. Biochemical characterization revealed a higher protein and lipid content both in N. gaditana and S. almeriensis which were grown on PM. Anyway, regardless of the growth medium used, N. gaditana presented higher protein and lipid content than S. almeriensis. Microbiological analysis shows no evidence of pathogen contamination (absence of Salmonella spp.; E. coli < 100 cfu/g), neither in microalgae produced on SM nor in those produced on PM. Growth performance, nutrient utilization and muscle composition in fish fed microalgae-supplemented diets were similar to those of the control group, showing they fulfilled the fish nutrient requirements for assuring sturgeon fingerlings growth and fillet nutritional quality. However, sturgeon fed-diets containing hydrolyzed N. gaditana biomass, grown on PM, reached greater average final weight then the other fish groups, included the control group. These results suggest the potential application of microalgae obtained by biorefinery as a protein and lipid source in practical diets for Siberian sturgeon (A. baerii). In particular, N. gaditana was revealed to be a potential functional ingredient in aquafeed, usable to improve the sustainability of microalgae ...